The Role Of Public Relations In Implementing The Corporate Social Responsibility Program At Pt. Xl Axiata - Muhammad Aidil Abror Nst (International Journal of Cultural and Social Science, 2021)
The Role of Public Relations in the Implementation of the Corporate Social Responsibility Program at PT. XL Axiata (Supervised by Muhammad Farid and Moeh. Iqbal Sultan). The aims of this study are: (1) to find out the reasons for PT. XL Axiata chooses education as its flagship CSR program; (2) to find out the actions to innovate and overcome obstacles by the PR and CSR team. This research was conducted at the head office of PT. XL Axiata, Jakarta. The informants of this study were people who were determined by purposive sampling, namely selected based on certain considerations that they were considered competent to answer the researcher's questions. Primary data was obtained through observation and in-depth interviews with informants. While secondary data is obtained through literature study in the form of books, journals, and so on related to the problem under study. The results of the study show that XL Future Leaders as a leading CSR program pays more attention to the development of outstanding young people from Sabang to Merauke with the tagline "XL Presentation Advancing Indonesia" which aims to create regeneration of future leaders. This study also found various kinds of innovations initiated by the XL Axiata CSR team in the implementation process, along with the way the CSR team overcomes the obstacles that arise. However, as the XL Future Leaders program grows, any problems that arise can be used as lessons for continuous improvement.